A Note on the Applications of Coding Theory - Mulatu, Lemma; Enya, Blessing; Keith, Lord (IJRDO -JOURNAL OF MATHEMATICS, 2018)
Communication and disc records are common in the society but sometimes there are errors in information transmission from one source to another. However, transmission has been made easier thanks to the discovery of the study of err-control code known as coding theory. Several methods like binomial coefficient and linear codes like Hamming codes play a role in ensuring the transmission of information through a noiseless channel. Even though binomial coefficient is a mathematical formula, it helps error-control smaller codes. Linear codes are easier and quick to use, but require a prime element. An example of linear codes is the Hammond codes and they are perfect because they attain the highest rates for codes within a minimum length distance of 3. Other examples of codes include repetition codes, cyclic codes, parity check and sum-0 codes, and generalized Reed-Solomon code.